Comprehensive Documentation of Mewahang: A First Linguistic Field Report - Sharma, Narayan P. (Nepalese Linguistics, 2022)
The Mewahang language belongs to the Kiranti branch of the Tibeto-Burman family and is predominantly spoken in Sankhuwasabha district of eastern Nepal. No linguistic fieldwork has been undertaken so far and the language remains undescribed. The paper characterizes a first comprehensive documentation of Mewahang, and presents data collection and ethnography.